Production and flow of desire among victims of S-Commerce shopping fraud in Indonesia - Ratna Azis Prasetyo; Rahma Sugihartati; Irfan Wahyudi (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2026)
Online shopping fraud is one of the most prevalent crimes in Indonesia. This study aims to uncover how someone experiences online shopping fraud using the conceptual framework of desire and the flow of desire by Deleuze and Guattari. Digital ethnography methods were used in this study to collect data through interviews with 42 online shopping fraud victims and participant observation in online shopping fraud victim communities on Facebook and other e-commerce platforms. The results of this study indicate that desires are produced by a desire machine, namely s-commerce, with various values, namely low prices, practicality, branded goods, which are decoded by online shopping fraudsters to trap victims. In addition, desires are channeled through an algorithmic work system that controls shopping behavior and decision-making by victims through the structure of online store’s trust values constructed through the number of followers, attractive displays, number of likes, online store visibility, and the influence of influencers. This study concludes that victims of shopping fraud crimes are brave not because of negligence, but rather the victims have been targeted through the s-commerce infrastructure, namely the algorithms and values that are built to influence the victim’s behavior and decisions.